Bentuk Linguistik Pada Papan Iklan (Billboard) Di Jalan Protokol Kota Bandung - Nurul Alfiah Ajeng Wahyu; Budi Hermawan; Ruswan Dallyono (Departement of Mathematics Education, 2024)
The development of billboards in the city of Bandung presents a significant challenge in optimizing public space. One of the factors that needs attention is the linguistic form used in creating billboards. The linguistic form in billboards can affect the effectiveness of communication and the public's understanding of the desired message. The purpose of this study is to analyze the linguistic form of billboards in public spaces in the city of Bandung and to determine how these linguistic forms affect communication effectiveness. This research uses a qualitative method by collecting data through observations on the city of Bandung's protocol roads where billboards are located. The results of the study show that the linguistic form of billboards in the city of Bandung can be in the form of verbal linguistics and there are several factors that influence communication effectiveness, namely linguistic form, typography, linguistic patterns, and language structure.